2007
DOI: 10.1063/1.2740579
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall effect at cleaved InSb surfaces and low-temperature annealing effect

Abstract: We have performed low-temperature in-plane magnetotransport measurements on twodimensional electron systems induced by deposition of Ag at in situ cleaved surfaces of p-type InSb. The quantum Hall effect was observed even at low magnetic fields around 2 T. The surface electron density and the electron mobility exhibit strong dependence on the Ag-coverage and the annealing temperature in the range of 15-40 K. The annealing effect suggests that the surface morphology strongly affects the properties of the two-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Photoelectron spectroscopy measurements have shown that the position of the Fermi level lies above the conduction-band minimum at cleaved (110) surfaces with various kinds of adsorbed materials [24,25]. Recently the present authors have performed magnetotransport measurements on inversion layers formed on cleaved surfaces of p-type InAs [26,27] and InSb [28] covered with submonolayers of Ag or alkali metals. The observed coverage dependence of the Hall mobility [26,28] indicates that adatoms strongly affect electron scattering in the inversion layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoelectron spectroscopy measurements have shown that the position of the Fermi level lies above the conduction-band minimum at cleaved (110) surfaces with various kinds of adsorbed materials [24,25]. Recently the present authors have performed magnetotransport measurements on inversion layers formed on cleaved surfaces of p-type InAs [26,27] and InSb [28] covered with submonolayers of Ag or alkali metals. The observed coverage dependence of the Hall mobility [26,28] indicates that adatoms strongly affect electron scattering in the inversion layer.…”
mentioning
confidence: 99%
“…Recently the present authors have performed magnetotransport measurements on inversion layers formed on cleaved surfaces of p-type InAs [26,27] and InSb [28] covered with submonolayers of Ag or alkali metals. The observed coverage dependence of the Hall mobility [26,28] indicates that adatoms strongly affect electron scattering in the inversion layer. It seems feasible to probe the properties of adsorbed ultrathin films through transport measurements of adjacent conduction layers.…”
mentioning
confidence: 99%
“…Furthermore, the H ⊥ dependence of the sheet resistance at low temperature is found to be almost independent of the presence of H . These results are explained by assuming an inhomogeneous superconducting state predicted for Rashba spin-split 2D systems.In order to measure the sheet resistance R sq of ultrathin films, we apply the experimental procedure developed for studies on adsorbate-induced surface inversion layers on InAs [13][14][15] and InSb [16]. In this work, we used a nondoped insulating GaAs single-crystal substrate so as not to create conduction channels in the substrate.…”
mentioning
confidence: 99%
“…In order to measure the sheet resistance R sq of ultrathin films, we apply the experimental procedure developed for studies on adsorbate-induced surface inversion layers on InAs [13][14][15] and InSb [16]. In this work, we used a nondoped insulating GaAs single-crystal substrate so as not to create conduction channels in the substrate.…”
mentioning
confidence: 99%
“…Previously, various studies have been done on annealing effect of InSb. [14][15][16] On glass, heat treating using furnace annealing (FA), rapid thermal annealing (RTA) or blue laser diode annealing (BLDA) 17 after forming InSb film using thermal evaporation method, the enhancement of the crystallinity of the InSb film and high carrier mobility can be expected.…”
Section: Introductionmentioning
confidence: 99%